Description of immature stages of Endochironomus pekanus (Kieffer) (Diptera, Chironomidae) - Li, Zixuan; Tang, Hongqu (Zootaxa, 2024)
The larva and pupa of Endochironomus pekanus (Kieffer, 1916) are described for the first time based on the pharate materials from China. Endotribelos redimiculum Qi, Shi, Lin et Wang, 2013 is newly synonymized with E. pekanus based on reexamination of the type material. New distribution records are also given for the species here.